AIoT Education Versus Conventional Teaching Toward Students Performance: A Systematic Literature Review - Herni Pujiati (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study investigates the relationships among AIoT Education, conventional teaching and student performance. The impact on the global education by employing qualitative type of methods in systematic literature reviews. The findings show that relationships among AIoT Education, conventional teaching confirming their importance in enhancing students’ performance.Research Methodology: systematic literature reviews and were collected through structured literature reviews, this research is a qualitative type of research.Results: The findings show that AIoT Education significantly complement conventional teaching, confirming their importance in enhancing student performance.Conclusions: AIoT education and conventional teaching both complement significantly toward student performance. AIoT education can build intellectual reciprocal partnerships with conventional teaching. AIoT education provides 24/7 services, while conventional teaching provides more humanistic approaches for students for online counseling and or coaching. AIoT education complements conventional teaching.  Conventional teaching will never be replaced by AIoT education. Subsequent studies are also encouraged to incorporate objective for upgrading students’ performance to complement the perceptual measures obtained from survey responses. Additionally, employing longitudinal or multi-country designs could provide a richer understanding of how regulatory evolution and AIoT education vs convention teaching shape the interplay between students’ performance, conventional teaching and AIot education over time.Limitations: This study limits only based upon systematic literature reviews and not empirical and purely only qualitative literature studies. Should be further observed for complete empirical studies in the future.Contributions: These results enrich the literature on AIoT education by integrating AIoT education with conventional teaching with the utmost output on student performance.